Medicinal plants popularly used in the Brazilian Tropical Atlantic Forest - Di Stasi, L. C.; Oliveira, G. P.; Carvalhaes, M. A.; Queiroz-Junior, M.; Tien, O. S.; Kakinami, S. H.; Reis, M. S. (Elsevier B.V., 2002)
A survey of medicinal plants used by rural and urban inhabitants of the three cities of the Tropical Atlantic Forest, Region of Vale do Ribeira, State of São Paulo, Brazil was performed by means of 200 interviews with medicinal plant users and extractors and, traditional healers. One hundred fourteen herbal remedies were recorded and the following information reported: Latin, vernacular and English names, plant part used, forms of preparation and application of the herbal remedies, medicinal or food uses, areas of plant collection, economic importance (when available) and other data. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: medicinal plants; ethnopharmacology; mata Atlantica; Tropical Atlantic Forest; traditional medicine; state of São Paulo; Brazil